Development of Acute Vogt–Koyanagi–Harada-like Syndrome during the Treatment Course with Vemurafenib for Metastatic Melanoma. (2nd April 2020) - Apivatthakakul, Atitaya; Kunavisarut, Paradee; Rothova, Aniki; Pathanapitoon, Kessara
ABSTRACT: Purpose : To report on ocular Vogt–Koyanagi–Harada (VKH)-like syndrome under vemurafenib treatment for metastatic melanoma. Design : A case report. Method : Description of clinical and imaging manifestations including fundus photography, fluorescein, and indocyanine green angiography. Results : A 46-year-old Thai female was diagnosed with metastatic melanoma of the skin and had been treated with multiple surgical excisions, radiotherapy, and vemurafenib (initial dose 480 mg orally twice daily, subsequently increased to maximum dose of 960 mg twice daily). After 6 months of vemurafenib use, she complained of bilateral redness and photophobia and was diagnosed with bilateral anterior uveitis, which was topically treated. Two weeks later, her visual acuity (VA) sharply deteriorated to 20/80 and counting fingers. Ocular examination at that stage stronly resembled acute VKH disease. She exhibited intraocular inflammation, and her fundus examination revealed bilateral optic disc swelling and serous retinal detachment. Fluorescein angiogram showed disc leakage and multiple pinpoint hyperfluorescence leakage spots and indocyanine green demonstrated multiple hypofluorescent spots. Oral prednisolone 30 mg/day was commenced while vemurafenib medication was ceased. Three weeks later, her vision improved, and serous retinal detachment subsided. However, her cutaneous melanoma recurred. Conclusions : Vemurafenib, a potential adjunct treatment for metastatic melanoma, was complicated by the development of panuveitis, papillitis, and multiple serous detachments. These ocular symptoms were similar to the presentation of acute VKH syndrome.